THE CONCEPT OF GIVING REWARDS AND PUNISHMENTS AND EMPLOYEE WORK DISCIPLINE OF PT. INDOLAKTO PASURUAN INDONESIA: Research Review - Panca Seputra, Yulius; Suparyo, Yasman; Kholil, Abdul; Ratnawati (Management Science Research Journal, 2024)
In the literature review of several previous studies, several conclusions have been obtained that rewards and punishments have an influence on the level of employee discipline, so that rewards and punishments... in a way significant influence performance employee in a way simultaneous and partial. Employees feel valued with gifts given by the company and that push motivate employee for work more hard and make more performance​ good. Employee take punishment with positive way​ as Lessons and making punishment as strength booster For Motivate they more many and create more performance​ Okay. The main stages of a scoping review are: (1) identifying research questions; (2) identifying relevant studies; (3) selecting studies; (4) creating data charts, and (5) compiling, summarizing, and reporting results. A 10-year time span (2014-2023), from the results of scoping observations, shows that most studies state that rewards and punishments have a significant effect on the level of employee work discipline. However, there are several research results that state that there is no influence between rewards and punishments on employee discipline at work, as stated by Ratu Mambrasa r ( 2021), who stated that present influential positive However No significant to discipline work employee . Keywords: Reward, Punishment, Work Discipline, Scope Review